Quantitative research on microscopic deformation behavior of Ti-6Al-4V two-phase titanium alloy based on finite element method. (13th April 2018) - Peng, Yan; Chen, Guoxing; Sun, Jianliang; Shi, Baodong
Abstract: The microscopic deformation of Ti-6Al-4V titanium alloy shows great inhomogeneity due to its duplex-microstructure that consists of two phases. In order to study the deformation behaviors of the constituent phases, the 2D FE model based on the realistic microstructure is established by MSC.Marc nonlinear FE software, and the tensile simulation is carried out. The simulated global stress-strain response is confirmed by the tensile testing result. Then the strain and stress distribution in the constituent phases and their evolution with the increase of the global strain are analyzed. The results show that the strain and stress partitioning between the two phases are considerable, most of the strain is concentrated in soft primary α phase, while hard transformed β matrix undertakes most of the stress. Under the global strain of 0.05, the deformation bands in the direction of 45° to the stretch direction and the local stress in primary α phase near to the interface between the two phases are observed, and they become more significant when the global strain increases to 0.1. The strain and stress concentration factors of the two phases are obviously different at different macroscopic deformation stages, but they almost tend to be stable finally.